Moderators of gene-outcome associations following traumatic brain injury. (November 2021) - Carmichael, Jai; Hicks, Amelia J.; Spitz, Gershon; Gould, Kate Rachel; Ponsford, Jennie
Highlights: Traumatic brain injury under complex polygenic influence. APOE, BDNF, and COMT key genes. Understanding factors that moderate genetic associations can improve patient care. Speculative mechanisms of gene-outcome moderation by age, biological sex, ethnicity. Recommendations for future genetics research in TBI and other populations. Abstract: The field of genomics is the principal avenue in the ongoing development of precision/personalised medicine for a variety of health conditions. However, relating genes to outcomes is notoriously complex, especially when considering that other variables can change, or moderate, gene-outcome associations. Here, we comprehensively discuss moderation of gene-outcome associations in the context of traumatic brain injury (TBI), a common, chronically debilitating, and costly neurological condition that is under complex polygenic influence. We focus our narrative review on single nucleotide polymorphisms (SNPs) of three of the most studied genes ( apolipoprotein E, brain-derived neurotrophic factor, and catechol-O-methyltransferase ) and on three demographic variables believed to moderate associations between these SNPs and TBI outcomes ( age, biological sex, and ethnicity ). We speculate on the mechanisms which may underlie these moderating effects, drawing widely from biomolecular and behavioural research ( n = 175 scientific reports) within the TBI population ( n = 72) and other neurological, healthy, ageing, and psychiatric populations ( n = 103). We conclude with methodological recommendations for improved exploration of moderators in future genetics research in TBI and other populations.